H.C.G (Human Chorionic Gonadotropin) versus Magnesium sulphate in suppression of preterm labour - Goswami, Prakriti; Agrawal, Veena (International Journal of Medical Research and Review, 2015)
Introduction: Preterm labour is a major healthcare problem throughout the world, it is a major cause of perinatal mortality and morbidity. Methods: Prospective comparative study conducted in the Department of Obstetrics & Gynaecology at Kamla Raja Hospital, Gwalior, M.P, from August 2011 to September 2012. Sample Size: 80. 50 patients were given H.C.G. and 30 were given Magnesium sulphate to suppress preterm labour. Statistical analysis done using Chi square test in SPSS software and p value < 0.05 was considered significant. Results: Mean duration between initiation of treatment & suppression of contractions was 3.1 hrs & 2.9 hrs in women receiving H.C.G. & Magnesium sulphate respectively (p value<0.0001). Mean prolongation of pregnancy was 31.4 days and 30.33 days in women receiving H.C.G. & Magnesium sulphate respectively (p value = 0.78). Average rate of labour within 48 hrs after beginning of treatment was 8% and 6.67%, in H.C.G. & Magnesium sulphate grp respectively, p value=0.43. None of the women receiving H.C.G. had any side effects, all 30 women receiving Magnesium sulphate had minor maternal side effects, p value (<0.0001). Mean birth weight was 2.35 kgs and 2.19 kgs respectively in women receiving H.C.G. and Magnesium sulphate reapectively, (p value = 0.22). Conclusion: Magnesium sulphate is better tocolytic drug, showing statistically significant lesser time between the initiation of treatment & suppression of contractions, as compared to H.C.G. Women receiving Magnesium sulphate suffered from minor side effects; however those treated with H.C.G. had no complaints.